Oxaliplatin added to fluorouracil-based preoperative chemoradiotherapy and postoperative chemotherapy of locally advanced rectal cancer (the German CAO/ARO/AIO-04 study): final results of the multicentre, open-label, randomised, phase 3 trial - Roedel, Claus; Graeven, Ullrich; Fietkau, Rainer; Hohenberger, Werner; Hothorn, Torsten; Arnold, Dirk; Hofheinz, Ralf-Dieter; Ghadimi, Michael; Wolff, Hendrik A.; Lang-Welzenbach, Marga; Raab, Hans-Rudolf; Wittekind, Christian; et al. (Lancet Oncology, 2015)
Preoperative chemoradiotherapy with infusional fluorouracil, total mesorectal excision surgery, and postoperative chemotherapy with fluorouracil was established by the German CAO/ARO/AIO-94 trial as a standard combined modality treatment for locally advanced rectal cancer. Here we compare the previously established regimen with an investigational regimen in which oxaliplatin was added to both preoperative chemoradiotherapy and postoperative chemotherapy.In this multicentre, open-label, randomised, phase 3 study we randomly assigned patients with rectal adenocarcinoma, clinically staged as cT3-4 or any node-positive disease, to two groups: a control group receiving standard fluorouracil-based combined modality treatment, consisting of preoperative radiotherapy of 50·4 Gy in 28 fractions plus infusional fluorouracil (1000 mg/m(2) on days 1-5 and 29-33), followed by surgery and four cycles of bolus fluorouracil (500 mg/m(2) on days 1-5 and 29); or to an investigational group receiving preoperative radiotherapy of 50·4 Gy in 28 fractions plus infusional fluorouracil (250 mg/m(2) on days 1-14 and 22-35) and oxaliplatin (50 mg/m(2) on days 1, 8, 22, and 29), followed by surgery and eight cycles of oxaliplatin (100 mg/m(2) on days 1 and 15), leucovorin (400 mg/m(2) on days 1 and 15), and infusional fluorouracil (2400 mg/m(2) on days 1-2 and 15-16). Randomisation was done with computer-generated block-randomisation codes stratified by centre, clinical T category (cT1-3 vs cT4), and clinical N category (cN0 vs cN1-2) without masking. The primary endpoint was disease-free survival, defined as the time between randomisation and non-radical surgery of the primary tumour (R2 resection), locoregional recurrence after R0/1 resection, metastatic disease or progression, or death from any cause, whichever occurred first. Survival and cumulative incidence of recurrence analyses followed the intention-to-treat principle; toxicity analyses included all patients treated. Enrolment of patients in this trial is completed and follow-up is ongoing. This study is registered with ClinicalTrials.gov, number NCT00349076.Of the 1265 patients initially enrolled, 1236 were assessable (613 in the investigational group and 623 in the control group). With a median follow-up of 50 months (IQR 38-61), disease-free survival at 3 years was 75·9% (95% CI 72·4-79·5) in the investigational group and 71·2% (95% CI 67·6-74·9) in the control group (hazard ratio [HR] 0·79, 95% CI 0·64-0·98; p=0·03). Preoperative grade 3-4 toxic effects occurred in 144 (24%) of 607 patients who actually received fluorouracil and oxaliplatin during chemoradiotherapy and in 128 (20%) of 625 patients who actually received fluorouracil chemoradiotherapy. Of 445 patients who actually received adjuvant fluorouracil and leucovorin and oxaliplatin, 158 (36%) had grade 3-4 toxic effects, as did 170 (36%) of 470 patients who actually received adjuvant fluorouracil. Late grade 3-4 adverse events in patients who received protocol-specified preoperative and postoperative treatment occurred in 112 (25%) of 445 patients in the investigational group, and in 100 (21%) of 470 patients in the control group.Adding oxaliplatin to fluorouracil-based neoadjuvant chemoradiotherapy and adjuvant chemotherapy (at the doses and intensities used in this trial) significantly improved disease-free survival of patients with clinically staged cT3-4 or cN1-2 rectal cancer compared with our former fluorouracil-based combined modality regimen (based on CAO/ARO/AIO-94). The regimen established by CAO/ARO/AIO-04 can be deemed a new treatment option for patients with locally advanced rectal cancer.German Cancer Aid (Deutsche Krebshilfe).
EVALuna2:15201